Intestinal Metaplasia of the Cardia is Associated With Barrett Esophagus and Esophageal Adenocarcinoma. Issue 2 (June 2022) - Kim, Tae Hun; Chandrasoma, Parakrama
The cardia, defined as the area distal to the endoscopic gastro-esophageal junction (GEJ), is rarely subject to biopsy in patients with gastro-esophageal reflux disease (GERD). In this study we examine the clinical significance of intestinal metaplasia (IM) found in a biopsy of the cardia. The epithelia in biopsies taken 1 cm distal to the endoscopic GEJ in 963 patients undergoing esophago-gastroduodenoscopy were classified into cardiac mucosa (CM) with IM, CM without IM, oxyntocardiac mucosa (OCM) and gastric oxyntic mucosa. The associations of these mucosal types with visible columnar lined esophagus (CLE) without IM, CLE with IM, and esophageal neoplasia proximal and within 2 cm distal to the endoscopic GEJ were determined. Cardiac mucosa with IM in a biopsy 1 cm distal to the endoscopic GEJ was present in 18 (21%) of the 86 patients with all visible CLE ( P < .01), in 16 (22%) of the 74 patients with visible CLE with IM (Barrett esophagus) ( P < .01), and in 12 (22%) of the 55 patients with neoplasia proximal and within 2 cm distal to the endoscopic GEJ ( P = .01). All other epithelial types had no such associations. The significant association of CM with IM in the cardia with visible CLE, visible CLE with IM, and esophageal neoplasia proximal and within 2 cm distal to the endoscopic GEJ indicates that CM with IM 1 cm distal to the endoscopic GEJ is a likely precursor of these entities. Identification of precursor lesions of CLE and esophageal neoplasia has the potential to stimulate new methods aimed at preventing Barrett esophagus and esophageal adenocarcinoma.